(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
This paper aims to understand the kampung as the informal fabric. Investigation into its patterns examines the relationship between informal and formal based on composition and proportion, while clarifying ‘the other’s’ perspective. As an architectural theory, heterotopia presents an analogy to stimulate new interpretations. As a study, the pattern updates the current condition of the kampung, while questioning the modern planning perspective. Qualitative and quantitative methods are combined to explain the pattern by producing maps as diagrams. Samples are extracted to highlight the kampung collective form as a dominant spatial configuration in Jakarta. Through calculation and projection, the research discovers a new kampung gesture; an informal aggregate that leads to the latest urban transformation of the kampung as the ephemeral of architecture. The novelty is a new understanding of the kampung’s distinctive figure and computation both as architecture and urban fabric. As a result, the kampung pattern suggests a combination of organic and semi-planned formation in the city, a hybrid nexus that grows and adapts according to its existing context.